N SITU IN SITU IN SITU MOISTURE CONSERVATION AND ZINC FERTILIZATION FOR RAINFED PIGEONPEA ( FOR RAINFED PIGEONPEA (CAJANUS CAJAN CAJANUS CAJAN CAJANUS CAJAN L.) - MATHUKIA, R. K; PONKIA, H. P (The Bioscan, 2016)
In a two-year field experiment conducted at Junagadh (Gujarat), moisture conservation practices (flat bed, alternate between-row subsoiling, between-row subsoiling, in-row subsoiling, and broad bed and furrow) and zinc fertilization (0, 5 and 10 kg Zn ha-1) were evaluated for pigeonpea (Cajanus cajan L.) grown under rainfed conditions. The results indicated that in-row subsoiling and broad bed and furrow reduced bulk density, conserved more soil moisture and significantly enhanced growth and yield attributes and nutrient uptake, which ultimately resulted in higher seed (1507 and 1443 kg ha-1) and stalk yields (3143 and 3017 kg ha-1) with higher net return (Rs. 15049 and 13991 ha-1) over flat bed. Zinc fertilization @ 5 kg ha-1 was found effective in increasing growth and yield attributes and nutrient uptake, and eventually gave higher seed yield (1412 kg ha-1) and stalk yield (2947 kg ha-1) along with higher net returns (Rs. 13775 ha1). Thus, the findings of present investigation indicated that inrow subsoiling or broad bed and furrow and application of 5 kg Zn ha-1 enhanced yield of pigeonpea and net returns under rainfed conditions.